KEABSAHAN PERCERAIAN PERSPEKTIF FIQH DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Siregar, Ramadhan Syahmedi (Hukum tata Negara/Siyasah, 2017)
Indonesia as a country of law and has set the rules for divorce in Law No. 1 of 1974 and in KHI (Compilation of Islamic Law). That should any couple seeking divorce refers to the existing rules. But, aside from the Law No. 1 In 1975 and KHI was no other rules are followed and adhered to by the Islamic community who wants a divorce, the classical Islamic law or jurisprudence, which in principle of Islamic jurisprudence (fiqh classic) did not arrange a divorce as it exists in the Act and KHI.Kata kunci: Hukum, perceraian, UU, Fiqh.